Methyl-β-cyclodextrin, an actin depolymerizer augments the antiproliferative potential of microtubule-targeting agents - Mundhara, Nikita (Sci Rep, 2019)
Methyl-β-cyclodextrin (MCD), an established pharmacological excipient, depolymerizes the actin cytoskeleton. In this work, we investigated the effect of MCD-mediated actin depolymerization on various cellular phenotypes including traction force, cell stiffness, focal adhesions, and intracellular drug accumulation. In addition to a reduction in the contractile cellular traction, MCD acutely inhibits the maturation of focal adhesions. Alteration of contractile forces and focal adhesions affects the trypsin-mediated detachment kinetics of cells. Moreover, MCD-mediated actin depolymerization increases the intracellular accumulation of microtubule-targeting agents (MTAs) by ~50% with respect to the untreated cells. As MCD treatment enhances the intracellular concentration of drugs, we hypothesized that the MCD-sensitized cancer cells could be effectively killed by low doses of MTAs. Our results in cervical, breast, hepatocellular, prostate cancer and multidrug-resistant breast cancer cells confirmed the above hypothesis. Further, the combined use of MCD and MTAs synergistically inhibits the proliferation of tumor cells. These results indicate the potential use of MCD in combination with MTAs for cancer chemotherapy and suggest that targeting both actin and microtubules simultaneously may be useful for cancer therapy. Importantly, the results provide significant insight into the crosstalk between actin and microtubules in regulating the traction force and dynamics of cell deadhesion.